Behavior intention to use of learning management system among Malaysian pre-service teachers: a confirmatory factor analysis - Zadeh, Sousan Baleghi; Mohd Ayub, Ahmad Fauzi; Mahmud, Rosnaini; Mohd Daud, Shaffe (Australian International Academic Centre, 2014)
Learning Management system is a type of Information system that many universities invest on to be integrated with their curriculum. Therefore, factors which make students accept or reject Learning Management System is crucial for educational managers of universities. The main purpose of the present study is to modify and validate a measurement model based on two models of Technology Acceptance Model and Fit Model. The proposed measurement model included five constructs of perceived ease of use, perceived usefulness, behavior intention to use, technical support and task-technology fit. The sample size of the study was 300 pre-service teachers studying at Universiti Putra Malaysia (UPM) and Universiti of Malaya (UM). The results of the study revealed that after deleting eleven items, the proposed measurement model was validated and fit. Therefore, the modified measurement model was able to present the theoretical patterns of the actual data.